Pricing behavior in partial cartels - Johannes Odenkirchen (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We analyze the pricing behavior of firms when explicit partial cartels have formed in experimental markets through communication. Using a repeated, asymmetric capacity constraint price game, we show that, in line with theory, a partial cartel is sufficient to increase market prices for all firms. Moreover, we find that prices of cartel insiders and outsiders are not necessarily on the same level what contradicts common theoretical predictions. This is because communication allows cartel members to overcome a potential coordination problem and enables an equilibrium in (joint) mixed strategies to emerge. The results therefore underline the importance of communication in explicit cartels and the resulting market outcomes.
Keywords: C92; D03; L13; L41; 330; partial cartels; explicit collusion; umbrella effects; experiments